Analisis Mekanisme Pembelajaran Daring Secara Sysnchronous dan Asysnchronous dimasa Pandemic Covid-19 di STMIK Sinar Nusantara - Iwan Ady Prabowo; Setiyowati .; Dwi Remawati (STMIK Sinar Nusantara, 2021)
Circular Number 05/SEK/STMIK-SN/IV/2020 in STMIK Sinar Nusantara Surakarta regulates implementation of learning, midterm exams, and even thesis / final exams. Hence, STMIK Sinar Nusantara took a policy for the implementation of synchronous learning and asynchronous learning. Synchronous learning (one time: teleconference, chatting) applies (1) Google Meeting by sinus.ac.id account, (2) Virtual meeting as Skype and Zoom, and (3) Discussion in Classroom. Meanwhile, asynchronous learning (time difference) uses (1) handouts, (2) tutorials, (3) videos, and (4) simple exercises. The purpose of this study was to determine the mechanisms in online learning (E-Learning) during Covid-19 Pandemic at STMIK Sinar Nusantara. This research only focuses on Synchronous and Asynchronous E-learning mechanism at STMIK Sinar Nusantara in even semester of 2019/2020. This research was conducted using 49 lecturers as respondents. The research method was descriptive statistical analysis. The results of the study by sampling 49 respondents as lecturers in online learning during Covid-19 Pandemic at STMIK Sinar Nusantara can be concluded that Synchronous learning (Conference by Google Meet, Skype, Zoom, Youtube Live, Umeetme) reached 57% and those who did not apply Synchronous learning (no conference) reached 43%. Meanwhile, the results of analysis in Asynchronous learning (handouts, tutorials, exercises / discussions, and videos) reached 88% and those who did not apply Asynchronous learning reached 12%.